Airway Inflammation and Inflammatory Biomarkers - Lim, Hui Fang; Nair, Parameswaran (Seminars in Respiratory and Critical Care Medicine, 2018)
Severe asthma is a complex disease consisting of different endotypes with different inflammatory and clinicopathological characteristics due to the heterogeneity of immune responses and smooth muscle dysfunction. There is an unmet clinical need to develop and to validate biomarkers that can differentiate between the asthma endotypes and guide clinical management, particularly since the availability of biologicals directed against T2 cytokines. The presence of a “Th2 endotype” is currently assessed in clinical practice using markers, such as eosinophil count in sputum or blood, fraction of exhaled nitric oxide, and immunoglobulin E. Individually or in combination, they may help to identify, for example, if the dominant effector protein is interleukin (IL) 5, IL13, or IgE. There is no reliable marker of a “non-Th2 endotype” although sputum neutrophil may provide some indication. The unbiased systems biology approach to severe asthma endotyping which integrates omics signatures and clinical data using large cohort studies may provide more comprehensive information than simple cellular measurements. Novel imaging techniques, such as hyperpolarized noble gas magnetic resonance imaging and computed tomography parametric response maps and metabolomics profiling in breath and other body fluids are also being evaluated as potential biomarkers to guide therapy and to assess prognosis.
Keywords: airway inflammation; biomarker; biologics; asthma endotypes; sputum eosinophil